Impact Of Customer Relationship Management In Small And Medium Enterprises In Malaysia - -, Dilruba (2007)
This research will try to investigate the impact of major CRM dimensions such as people, process and technology on the overall business performance in SMEs in Malaysia. Due to its growing importance, the SMEs will be considered as the focus of the study.